SONG PREFERENCES IN MUSIC LEARNING IN PRIMARY SCHOOLS: A STUDY OF TEACHERS' HABITUS AND CULTURAL CAPITAL BASED ON PIERRE BOURDIEU'S APPROACH - Arhamuddin Ali; Evi Faujiah; Risky Dwiprabowo; Dyah Anungrat Herzamzam; Aufaa Luthfiah Murtiono; Radhana Oktaviona; Matheus Musen Ola (Prima Magistra: Jurnal Ilmiah Kependidikan, 2026)
This research is motivated by the importance of music, especially songs, in elementary school learning, which not only serves as entertainment but also functions as a pedagogical medium that supports the learning process and the formation of students' character. The purpose of this study is to analyze how music arts teachers use songs in their teaching and to examine the interaction among habitus, cultural capital, and the school arena in music education practice. The research uses a qualitative, case study design following the Creswell model, conducted in SD Jakarta Timur Region II during the 2025/2026 semester, with music teacher subjects selected through purposive sampling. Data was obtained through observation, in-depth interviews, and documentation studies, then analyzed qualitatively through the stages of data reduction, presentation, and verification. The results showed that the interaction among habitus, cultural capital, and curriculum demands influenced teachers' song choices in elementary school music learning. The teacher's personal habitus and experience encourage the use of both traditional and popular children's songs, while institutional cultural capital emphasizes national and thematic songs. On the other hand, contemporary social dynamics open up space for teachers to adopt songs from digital media to be more in tune with students' world.